2023
DOI: 10.1158/2159-8290.cd-22-0869
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Biased T-cell Exhaustion Drives Differential Immune Responses in Glioblastoma

Abstract: Sex differences in glioblastoma (GBM) incidence and outcome are well recognized, and emerging evidence suggests that these extend to genetic/epigenetic and cellular differences, including immune responses. However, the mechanisms driving immunological sex differences are not fully understood. Here, we demonstrate T cells play a critical role in driving GBM sex differences. Male mice exhibited accelerated tumor growth, with decreased frequency and increased exhaustion of CD8+ T cells in tumor. Furthermore, a hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 48 publications
(52 reference statements)
0
19
0
Order By: Relevance
“…In complement, Li et al, found that ibrutinib reduced CD8 + T cell exhaustion both in the in vitro setting and in BTK deficient mice, specifically by downregulating inhibitory receptors and increasing cytokine production [ 51 ]. The presence of T cell inhibitory signaling has been implicated in assistance with disease progression in glioblastomas thus further studies are warranted to further delineate the influence of BTK/BMX inhibition on T-cell infiltration, microglial behaviors and cytokine production within immunocompetent models [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In complement, Li et al, found that ibrutinib reduced CD8 + T cell exhaustion both in the in vitro setting and in BTK deficient mice, specifically by downregulating inhibitory receptors and increasing cytokine production [ 51 ]. The presence of T cell inhibitory signaling has been implicated in assistance with disease progression in glioblastomas thus further studies are warranted to further delineate the influence of BTK/BMX inhibition on T-cell infiltration, microglial behaviors and cytokine production within immunocompetent models [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…KDM6B deficiency inhibits secretion of immunosuppressive mediators such as MAF BZIP transcription factor B (MAFB), suppressor of cytokine signaling 3 (SOCS3), and signal regulatory protein alpha (SIRPA), thereby enhancing the efficacy of anti-PD-1/programmed cell death 1 ligand 1 (PD-L1) therapy [ 52 ]. In humans, presence of X chromosome inactivation escape gene KDM6A [ 53 ] results in lower CD8 + T cell levels in male GBM microenvironments than in female GBM microenvironments [ 54 ]. Moreover, T cells in the male GBM microenvironment are more prone to exhaustion.…”
Section: The Immune Regulation In Glioblastomamentioning
confidence: 99%
“…Combination therapy involving DNA damage response inhibitors (DDRi) and RT in H3.3-G34R pHGG mice can significantly increase median survival [ 68 ]. Table 1 shows the epigenetic alterations associated with immune regulation in GBM [ 49 – 52 , 54 , 63 , 66 , 68 – 84 ].…”
Section: The Immune Regulation In Glioblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor-intrinsic sex differences include differences in enhancer landscapes, glutamine metabolism, and oncogenic transformation 8,9 . Tumor-extrinsic factors contributing to sex bias include microglial activation and anti-tumor immunity 10,11 . However, the mechanisms underlying these sex-specific differences remain unknown.…”
Section: Introductionmentioning
confidence: 99%